Rancang Ulang Meja dan Kursi untuk Kelas 1 di SMK Negeri 3 Medan dengan Menggunakan Metode RULA dan Pahl & Beitz - Ritonga, Wahyu Hidayat; Azis Syarif, Abdul; Walady Utama, Denny (SURYA TEKNIKA, 2024)
SMKN 3 students use tables and chairs for approximately six hours a day during the teaching and learning process. If the sitting posture of this student is not correct, such as leaning forward or a footrest that is too high, of course it can cause pain in the waist and pain in the knees. This study aims to make tables and chairs that are comfortable for use by students of SMKN 3 MEDAN and to find out the design for ergonomic tables and chairs so that when using tables and chairs students do not feel pain in the waist or other complaints. This study resulted in a new table and chair design. Based on the calculation results, the results of the new chair dimensions were as follows: table height 71.15 cm, table length 58 cm, table width cm, seat cushion width 32 cm, seat cushion length 43 cm, height seat cushion 40 cm, backrest height 54 cm. The dimensions of the bag are 10 cm for width, 40 cm for height, 30 cm for length. Therefore the tables and chairs that have been redesigned are in accordance with the anthropometry of students at SMKN 3 MEDAN